Student perception of teacher encouragement of self-regulated learning and its relationship with self-regulation learning strategies - Šimić Šašić, Slavica; Atlaga, Maša (Frontiers in Education, 2024)
IntroductionSelf-regulated learning significantly impacts academic achievement and learning effectiveness; however, a significant portion of students do not engage in optimal self-regulated learning. Teachers can influence self-regulated learning in various direct and indirect ways, such as teaching students effective learning strategies or structuring the learning environment. Research indicates that teachers moderately encourage self-regulated learning, with direct/explicit teaching methods being underutilized despite their stronger contribution to fostering learning self-regulation. Teachers often overestimate their encouragement of learning self-regulation compared to students’ perceptions. There is a scarcity of research on encouraging self-regulated learning in teaching practices, particularly from the students’ perspective. Hence, the aim of this study was to examine how students perceive teacher encouragement of self-regulated learning and its association with their own self-regulated learning.MethodsThe research was conducted on a sample of 2,154 students who assessed the teacher’s encouragement of self-regulated learning and their own self-regulated learning in a specific subject.ResultsStudents perceive that teachers moderately to relatively highly encourage self-regulated learning. Statistically significant moderate correlations were found between students’ assessments of learning self-regulation and the encouragement of self-regulated learning. Girls perceive that teachers encourage self-regulated learning to a greater extent, as do secondary school students compared to primary school ones. Teacher encouragement of self-regulated learning explains from 0 to 32% of the variance in self-regulated learning strategies. Defensive self-regulation strategies (avoiding work, self-handicapping, and focusing on minimal demands) are explained to the least extent, while proactive self-regulation strategies (orientation towards acquisition, elaboration, and goal setting) are explained to a considerably greater degree.DiscussionThe research results suggest that students’ perception of teacher encouragement of self-regulated learning is a significant predictor of learning self-regulation in students. The data obtained in the research contributes to understanding the encouragement of self-regulated learning from the students’ perspective and highlights the importance of students’ assessments of encouragement of self-regulated learning.